First report of congenital Neospora caninum encephalomyelitis in two newborn calves in the Argentinean Pampas - Micheloud, Juan Francisco; Moore, Prando Dadin; Canal, Ana María; Lischinsky, Lilian Haydee; Hecker, Yanina Paola; Canton, German Jose; Odriozola, Ernesto Raul; Odeon, Anselmo Carlos; Campero, Carlos Manuel (2017)
Bovine neosporosis is a parasitic disease of major concern in cattle industry worldwide. Although abortion is the more frequent clinical presentation, sporadic congenital clinical bovine neosporosis has been scarcely reported in newborn calves. Neospora caninum encephalomyelitis was diagnosed in two of 314 newborn calves submitted for necropsy and laboratory analysis between 2000 and 2014. The two new born calves had limb dysfunction, loss of conscious proprioception and ataxia. Protozoal multifocal nonsuppurative encephalomyelitis was observed and diagnosis was confirmed using serology, immunohistochemistry and PCR. This is the first report of clinical congenital neosporosis in calves from Argentina.